The Religious System of China, its Ancient Forms, Evolution, History and Present Aspect, Manners, Customs and Social Institutions Connected Therewith. Vol. 5, Book 2 On the Soul and Ancestral Worship. Part II : Demonology; Part III : Sorcery - De Groot, J. J. M. (Taipei : Ch'eng-wen, 1969)
Part II : Demonology
On the Omnipresence and Multitude of Spectres
On Spectres of Mountains and Forests
On Water-Demons
On Ground-Demons
On Animal-Demons
Tiger-Demons
Wolf-Demons
Dog-Demons
Fox-Demons
Various Wild Mammals as Demons
Diestic Animals in Demonology
Reptile-Spectres
Bird-Demons
Piscine Devils
Insect as Demons
On Plant-Demons
Lifeless Things as Spectres
Demonism in Pathology
On Suicide-Spectres
Spectres with a Material Body. Vampirism
Anthropophagous and Necrophagous Spectres
On Ghosts and Spectres appearing at Deaths
Black Calamities
Additional Particulars
The World of Spectres a Copy of that of Man
Part III : Sorcery
Infliction of Evil by means of one's own Soul or that of a Quadruped
Sorcery by means of small Reptiles and Insects
Remedies for K u
Infliction of Evil by means of Human Souls
Sorcery by means of Soul of Objects
Other Forms of Sorcery